2016
DOI: 10.1002/jbt.21824
|View full text |Cite
|
Sign up to set email alerts
|

Neuro‐Modulation of Immuno‐Endocrine Response Induced by Kaliotoxin of Androctonus Scorpion Venom

Abstract: Kaliotoxin (KTX), a specific blocker of potassium channels, exerts various toxic effects due to its action on the central nervous system. Its use in experimental model could help the understanding of the cellular and molecular mechanisms involved in the neuropathological processes related to potassium channel dysfunctions. In this study, the ability of KTX to stimulate neuro-immuno-endocrine axis was investigated. As results, the intracerebroventricular injection of KTX leads to severe structural-functional al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Another study conducted by Malih et al 38 showed neuronal darkness, cellular atrophy and atypia, associated with edema and hemorrhages as a result of envenomation by sLD of the Androctonus mauretanicus mauretanicus scorpion, whereas, the toxic fraction of Am venom expressed a neuronal constriction, congestion, vasodilation and edema following intra-cerebroventricular (ICV) administration of a sLD. 39 Experimentally, Ladjel-Mendil et al 14 observed similar damages (edema, hemorrhage, necrosis…) with ICV injection of sLD of purified Kaliotoxin from Androctonus australis hector scorpion venom.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Another study conducted by Malih et al 38 showed neuronal darkness, cellular atrophy and atypia, associated with edema and hemorrhages as a result of envenomation by sLD of the Androctonus mauretanicus mauretanicus scorpion, whereas, the toxic fraction of Am venom expressed a neuronal constriction, congestion, vasodilation and edema following intra-cerebroventricular (ICV) administration of a sLD. 39 Experimentally, Ladjel-Mendil et al 14 observed similar damages (edema, hemorrhage, necrosis…) with ICV injection of sLD of purified Kaliotoxin from Androctonus australis hector scorpion venom.…”
Section: Discussionmentioning
confidence: 91%
“…During a scorpion sting, a very small amount of venom is inoculated causing multiple symptom that can be digestive, vegetative, neurological, cardiovascular, and/or respiratory signs 13,14 and can eventually lead to death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation